2023
DOI: 10.1186/s40352-023-00216-x
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 vaccine acceptance among individuals incarcerated in Connecticut state jails

Abstract: Background Vaccine hesitancy is common among incarcerated populations and, despite vaccination programs, vaccine acceptance within residents remains low, especially within jails. With the goal of assessing the Connecticut DOC’s COVID-19 vaccine program within jails we examined if residents of DOC operated jails were more likely to become vaccinated following incarceration than in the community. Specifically, we conducted a retrospective cohort analysis among people who spent at least one night … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A large US study of 126 413 PEI reported a slightly higher rate of full vaccination (33.4%) compared with the general population (29.5%) 65. Incarcerated residents also had more time eligible for vaccination in the community (79 days, IQR: 41–183) than in jail (14 days IQR: 3–31) and were 12.5 times (95% CI 10.2 to 15.3) more likely to consent to and receive vaccination while incarcerated than before incarceration 66. Conversely, a Public Health Scotland report found that uptake of a full course of COVID-19 vaccine in PEI was lower than in the public 67.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A large US study of 126 413 PEI reported a slightly higher rate of full vaccination (33.4%) compared with the general population (29.5%) 65. Incarcerated residents also had more time eligible for vaccination in the community (79 days, IQR: 41–183) than in jail (14 days IQR: 3–31) and were 12.5 times (95% CI 10.2 to 15.3) more likely to consent to and receive vaccination while incarcerated than before incarceration 66. Conversely, a Public Health Scotland report found that uptake of a full course of COVID-19 vaccine in PEI was lower than in the public 67.…”
Section: Resultsmentioning
confidence: 95%
“…65 Incarcerated residents also had more time eligible for vaccination in the community (79 days, IQR: 41-183) than in jail (14 days IQR: 3-31) and were 12.5 times (95% CI 10.2 to 15.3) more likely to consent to and receive vaccination while incarcerated than before incarceration. 66 Conversely, a Public Health Scotland report found that uptake of a full course of COVID-19 vaccine in PEI was lower than in the public. 67 This finding was Open access echoed by a Danish whole population study demonstrating that PEI during 2020 in Denmark were half as likely to complete a full course of COVID-19 vaccination as the general population (aIRR 0.5 95% CI 0.5 to 0.5).…”
Section: Mortality From Covid-19 In Peimentioning
confidence: 99%